2022
DOI: 10.1111/joa.13790
|View full text |Cite
|
Sign up to set email alerts
|

Synchondrosis fusion contributes to the progression of postnatal craniofacial dysmorphology in syndromic craniosynostosis

Abstract: Syndromic craniosynostosis (CS) patients exhibit early, bony fusion of calvarial sutures and cranial synchondroses, resulting in craniofacial dysmorphology. In this study, we chronologically evaluated skull morphology change after abnormal fusion of the sutures and synchondroses in mouse models of syndromic CS for further understanding of the disease. We found fusion of the inter-sphenoid synchondrosis (ISS) in Apert syndrome model mice (Fgfr2 S252W/+ ) around 3 weeks old as seen in Crouzon syndrome model mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 67 publications
1
7
0
Order By: Relevance
“…[3] Furthermore, it has been suggested in previous studies that the ISS and SOS in the cranial base contribute significantly to the growth of the cranial vault. [2,4] Similar to this, in the present study, it is suggested that the sphenoid bone contributes to the cranial vault curvature.…”
Section: Relationship Between Cranial Vault Angle and Sphenoid Bone L...supporting
confidence: 90%
See 1 more Smart Citation
“…[3] Furthermore, it has been suggested in previous studies that the ISS and SOS in the cranial base contribute significantly to the growth of the cranial vault. [2,4] Similar to this, in the present study, it is suggested that the sphenoid bone contributes to the cranial vault curvature.…”
Section: Relationship Between Cranial Vault Angle and Sphenoid Bone L...supporting
confidence: 90%
“…ISS and SOS contribute significantly to the growth of the cranial vault and upper face as well as the skull base. [ 2 , 4 ] The cranial vault consists of frontal bones, parietal bones, the squamous parts of the temporal bone, and the interparietal part of occipital bone.…”
Section: Introductionmentioning
confidence: 99%
“…A computer simulation study suggests that cranial sutures are positioned in the skull where higher patterns of strain are experienced [122]. The premature fusion of one suture, which occurs in craniosynostosis, may result in increased irregular loading on other parts of the skull, possibly causing abnormal bone growth and malformations [124]. Developmentally, open cranial sutures are the major sites of bone growth and behave as signalling centres for regulating the balance between the proliferation of osteoblast precursors and osteogenic differentiation [125,126].…”
Section: Revisiting the Homology Of The Mammalian Skullmentioning
confidence: 99%
“…Suture closure and bone fusion occur when the fibrous borders between bones become ossified and closed owing to the activity of the Hedgehog, Fgf , Wnt and Pthlh signalling pathways [127,128]. To maintain their function as bone growth sites, sutures are required to remain patent, whereas the premature closure of sutures leads to growth abnormalities in the skull [124,126,129]. Evolutionarily, extra suture closures induce bone fusions, resulting in the apparent decrease of skull bone elements, as observed in the origin of the mammalian interparietal.…”
Section: Revisiting the Homology Of The Mammalian Skullmentioning
confidence: 99%
See 1 more Smart Citation